Myeloid Sarcoma Presenting with Leukemoid Reaction in a Child Treated for Acute Lymphoblastic Leukemia - Aylin Canbolat Ayhan; Cetin Timur; Seyma Sonmez; Ebru Zemheri; Asım Yoruk (Case Reports in Hematology)
Background. Myeloid sarcoma is an extramedullary neoplasm of immature myeloid cells. Our study reports a presentation of myeloid sarcoma which presented with severe leukemoid reaction as a secondary malignancy in a patient who was treated for acute lymphoblastic leukemia previously. The case emphasizes the difficulties in diagnosis of patients who do not have concomitant leukemia. Case Presentation. A 6-year-old girl who was treated for acute lymphoblastic leukemia previously presented with fatigue, paleness, and hepatosplenomegaly. Peripheral blood smear and bone marrow aspirate examination did not demonstrate any blasts in spite of severe leukemoid reaction with a white cell count 158000/mm3. FDG/PET CT revealed slight uptake in cervical and supraclavicular lymph nodes. Excisional lymph node biopsy was performed from these lymph nodes and it showed myeloid sarcoma. Conclusion. Myeloid sarcoma can develop as a secondary malignancy in children who are treated for acute lymphoblastic leukemia. It can be associated with severe leukemoid reaction and diagnosis may be difficult if there is not concomitant leukemia. PET/CT is helpful in such cases.